Controller design of an elbow exoskeleton for upper limb rehabilitation - Roy, Rupal (Kulliyyah of Engineering, International Islamic University Malaysia, 2019)
Researchers of physical rehabilitation are reluctant to adopt manual hands-on approach in modern era. Consequently, the negative impact goes on the physiotherapy treatment and other physical exercises. Conversely, the development of rehabilitation in robotic approach is achieving popularity among the researchers. However, this research work was introduced with an exoskeleton robot in order to resolve the physical rehabilitation of human upper limb specifically on angle joint of elbow. The work has been developed to evaluate the movement of the elbow in simulation environment and experimental. Computer Aided Design (CAD) drawing has been done. As a controller, Proportional integral derivative (PID) has been implemented on the system for error-free and smooth performance. Beside that two different control strategies have been developed in order to control the moment of the robot properly. One of the controllers accumulates forces on the user's limb to move the exoskeleton that helps user movements. One the other hand Proportional integral derivative (PID) control assists the exoskeleton for the movement of the limb along with a predefined trajectory. The work has been evaluated based on simulation results at the beginning that encourages to advance the work. The result obtained from simulation works were satisfactory and subsequently, the simulated works have been validated by hardware performance. The completed work opens the opportunity for robotic augmentation in physical rehabilitation subjectively